The Phenomenon of Augmented Reality Face Filter Usage on Instagram Among Communication Science Students of the 2019 Cohort at Pattimura University, Ambon - Sulaiman, Yaser Bin; Lestaluhu, Said; Husein, Muhammad Iqbal (Baileo: Jurnal Sosial Humaniora, 2023)
This study aims to describe the reasons, actions, and meanings behind the use of augmented reality (AR)-based facial filters on Instagram by Communication Science students from the 2019 cohort at Pattimura University, Ambon. The research employs a qualitative method with a phenomenological approach to understand social actions and the meanings embedded within them. Informants were selected purposively, consisting of active Instagram users, identified based on the intensity of their platform usage. Data were collected through in-depth interviews, observations, and document analysis. The results of the study indicate that the primary motives for using facial filters include affective motives, the need for reputation, and the drive to maintain existence in the digital space. Each of these motives influences user behavior, ultimately reflecting how individuals interpret life satisfaction through their interactions with AR technology. This study contributes new insights to social and humanities research, particularly regarding the role of AR technology in shaping social experiences and the digital identities of young generations. The novelty of this research lies in uncovering the dynamics of AR filter usage as a form of self-expression and digital image creation. The study recommends further research to explore the impact of AR technology on social interaction patterns and the construction of digital identities, while also offering new perspectives for the development of communication theory in the digital era.